Processions, Architecture, and the Space In-Between: Some Observations about Sculpted Moche Pottery. (2nd January 2016) - Wiersema, Juliet
Abstract : The focus of procession, in the ancient Andes and elsewhere, is generally on movement. A handful of Moche ceramic vessels, however, suggest that stasis was also an important part of processional activity. This article presents visual evidence from Moche ceramic vessels and Moche architectural remains to suggest that Moche artisans intentionally included references to pauses in ritual activity. These pauses are given tangible form on representations where two-dimensional processional movement intersects with three-dimensional architectural structures. Appearing as recessed or depressed spaces, they are located squarely in the boundary between processional movement and architectural destination. While these features, in both art and architecture, have been largely overlooked, their inclusion in Moche art indicates they had a decided function in Moche ritual activity. Their appearance in art and architecture alerts us to, as well as concretizes, an aspect of procession which is difficult to recognize in the archaeological record: thresholds of transition, or liminal space. These features illuminate for us not only a space but also a moment. By giving concrete form to this feature, Moche artisans communicated the importance of liminal or transitional moments in Moche procession.